Documentation of feeding associations of the Purple Gallinule, Porphyrio martinica (Aves: Rallidae), and the Wattled Jacana, Jacana jacana (Aves: Jacanidae), with the capybara, Hydrochoerus hydrochaeris (Mammalia: Hydrochaeridae), facilitated by its bea - Schunck, Fabio; dos Santos, Estevão Pereira Vicente (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
The capybara, Hydrochoerus hydrochaeris, is known to form feeding associations with different bird species. One such association involves a beating behavior, in which the animal moves through the environment while birds follow it to capture insects that are disturbed. We documented this behavior in a wetland area of Southeast Brazil, involving the already known association between the capybara and the Wattled Jacana, Jacana jacana, and a previously unknown association between the capybara and the Purple Gallinule, Porphirio martinica. The latter also fed on capybara ticks, another novel association. Expanding knowledge and documenting ecological relationships between mammals and birds contributes to both the natural history of these organisms and ecological and public health issues, as ticks are vectors of spotted fever in Southeast Brazil.
Keywords: Brazil; Guarapiranga Reservoir; Animal behavior; Public health; Spotted fever